2020
DOI: 10.1177/0885066620976525
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Inhaled Epoprostenol in Respiratory Failure due to COVID-19

Abstract: Background: Inhaled pulmonary vasodilators are used as adjunctive therapies for the treatment of refractory hypoxemia. Available evidence suggest they improve oxygenation in a subset of patients without changing long-term trajectory. Given the differences in respiratory failure due to COVID-19 and “traditional” ARDS, we sought to identify their physiologic impact. Methods: This is a retrospective observational study of patients mechanically ventilated for COVID-19, from the ICUs of 2 tertiary care centers, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 40 publications
6
48
1
Order By: Relevance
“…This indicates, similar to what was found in the current series, that those select patients will positively respond to iEpo therapy with significant improvements in oxygenation [30]. Another retrospective study by Sonti et al(2021) looked at 80 patients who received iEpo and had P/F ratios measured. Patients were initiated when they had severe ARDS, as evidenced by a P/F ratio of 92 mmHg at baseline.…”
Section: Discussionsupporting
confidence: 84%
“…This indicates, similar to what was found in the current series, that those select patients will positively respond to iEpo therapy with significant improvements in oxygenation [30]. Another retrospective study by Sonti et al(2021) looked at 80 patients who received iEpo and had P/F ratios measured. Patients were initiated when they had severe ARDS, as evidenced by a P/F ratio of 92 mmHg at baseline.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, PGE 2 is mostly anti‐inflammatory via the EP 2 and EP 4 receptors 29 and PGI 2 is a recognized microvasculature dilator. In that respect, a retrospective observational study showed that the administration of PGI 2 (epoprostenol) was effective at improving the PaO 2 /FiO 2 ratio in 50% of COVID‐19 patients 30 . Therapies targeting the prostaglandin pathway are numerous and usually effective at controlling inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the baseline characteristics were markedly different and early administration of inhalation might be beneficial. Sonti et al [ 27 ] also reported clinically significant improvement in PaO 2 /FiO 2 after the initiation of inhaled epoprostenol in 50% of mechanically ventilated patients. Combination use of inhaled epoprostenol and prone positioning in COVID-19 patients with mechanical ventilation with refractory hypoxemia showed improved oxygenation compared with each treatment individually [ 28 ].…”
Section: Main Textmentioning
confidence: 99%